Proposed Business Strategy for Customer Experience Management Implementation to Support Airport’s Non-Aeronautical Business Case Study: PT Angkasa Pura Indonesia - I Gst. Ngr. Agung Bayu Ditaprawira; Harimukti Wandebori (Green Publisher Indonesia, 2026)
Customer experience has become a prominent focus for airport operators to meet passengers' expectations of seamless, comfortable, and memorable journeys. In September 2024, two major airport operators in Indonesia merged into PT Angkasa Pura Indonesia (API), now operating 37 airports across the nation. As a State-Owned Enterprise, API is mandated not only to become an agent of development and value creator but also to serve as the face and pride of the nation. To fulfill these mandates, API must develop a holistic strategy that enhances customer experience while supporting business sustainability. This study reviews literature on business strategy and customer experience management, examines the company's current condition, and conducts research to understand passenger profiles and their perceptions of key touchpoints during departure journeys. Market analysis, internal company assessments, and external environment evaluations were conducted to gain comprehensive insights. Research findings reveal that all touchpoints significantly impact customer satisfaction and willingness to spend. The study proposes an integrated customer experience playbook as a business-level strategy to standardize customer experience understanding and practices company-wide across all airports. This strategy remains flexible, allowing individual airports to develop tailored improvements according to specific touchpoint conditions and financial capabilities. The playbook also serves as a reference for functional units—operations, commercial, and human capital—to develop strategies aligned with customer experience objectives. Additionally, the study recommends implementing partnership models to upgrade service quality at airports with lower costs while potentially opening new revenue streams.